(3cJGH GdTWQfLs
(3ChdgG (B:s
(3PcQ GdYGOdi CSHGHkG ai hVY GdTWQfL YOI hQO Ydjg CHh HcQ GdUhdi aPcQfG HYV eG PcQfGg GdYOdi heG hQO Ydjg GdUhdi s
(3BNQgG (B:s
(3bGd GdUhdi gPG ef CMSf GdOSJ hCObgG Je HMeO Gddg hYfg hGddg SHMGfg hJYGdi CYde s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CdYGH JjehQ (B7) s
Keywords: (3GdTWQfLs